Coping With Infrastructural Deprivation Through Collective Action Among Rural People in Nigeria - Shittu R. Akinola (Nordic Journal of African Studies, 2007)
The failure of the state to address the problems of rural infrastructure in rural areas of Nigeria led to the adoption of self-governing techniques by the people through collective action. The study shows that rural people organized themselves based on appropriate institutional arrangements, mutual agreements and shared understanding; and planned and executed public goods and services that directly touched the lives of their people. The paper found that rural communities in south-western Nigeria through self-organized arrangements provided rural facilities at the cost of N26,204,000.00 ($1,546,071.7) (i.e. 98.3%) of the total figure thus constituting the prime mover for rural facilities development, while Local Governments contributed N450,000.00 ($20,452) (i.e. 1.7%) on the same facilities. The concern is that if these institutions are so accountable to their members, we should begin to conceptualize how they can be used to re-constitute order from the bottom up and to complement the state structure of governance.